Digital leadership: Motivating online workers - Petra Nieken (IZA World of Labor, 2022)
Remote work and digital collaborations are prevalent in the business world and many employees use digital communication tools routinely in their jobs. Communication shifts from face-to-face meetings to asynchronous formats using text, audio, or video messages. This shift leads to a reduction of information and signals leaders can send and receive. Do classical leadership and communication techniques such as transformational or charismatic leadership signaling still work in those online settings or do leaders have to rely on transactional leadership techniques such as contingent reward and punishment tools in the remote setting?
Keywords: C93; D91; M12; M21; M50; 330; digital leadership; remote work; gig economy; virtual leadership